Atomic force microscopy and graph analysis to study the P-cadherin/SFK mechanotransduction signalling in breast cancer cells. Issue 46 (16th November 2016) - Ribeiro, A. S.; Carvalho, F. A.; Figueiredo, J.; Carvalho, R.; Mestre, T.; Monteiro, J.; Guedes, A. F.; Fonseca, M.; Sanches, J.; Seruca, R.; Santos, N. C.; Paredes, J.
Abstract : Atomic force microscopy and cell network diagrams were used to measure the epithelial biomechanical properties and structural organization induced by P-cadherin/SFK signaling in breast cancer cells. Abstract : Physical forces mediated by cell–cell adhesion molecules, as cadherins, play a crucial role in preserving normal tissue architecture. Accordingly, altered cadherins' expression has been documented as a common event during cancer progression. However, in most studies, no data exist linking pro-tumorigenic signaling and variations in the mechanical balance mediated by adhesive forces. In breast cancer, P-cadherin overexpression increases in vivo tumorigenic ability, as well as in vitro cell invasion, by activating Src family kinase (SFK) signalling. However, it is not known how P-cadherin and SFK activation impact cell–cell biomechanical properties. In the present work, using atomic force microscopy (AFM) images, cell stiffness and cell–cell adhesion measurements, and undirected graph analysis based on microscopic images, we have demonstrated that P-cadherin overexpression promotes significant alterations in cell's morphology, by decreasing cellular height and increasing its area. It also affects biomechanical properties, by decreasing cell–cell adhesion and cell stiffness. Furthermore, cellular network analysis showed alterations in intercellular organization, which is associated with cell–cell adhesion dysfunction, destabilization of an E-cadherin/p120ctn membrane complex and increased cell invasion. Remarkably, inhibition of SFK signaling, using dasatinib, reverted the pathogenic P-cadherin induced effects by increasing cell's height, cell–cell adhesion and cell stiffness, and generating more compact epithelial aggregates, as quantified by intercellular network analysis. In conclusion, P-cadherin/SFK signalling induces topological, morphological and biomechanical cell–cell alterations, which are associated with more invasive breast cancer cells. These effects could be further reverted by dasatinib treatment, demonstrating the applicability of AFM and cell network diagrams for measuring the epithelial biomechanical properties and structural organization.